Learner's Perceived Benefits in Employing Proofreader as a Vehicle for Developing his English Writing Competency - Achmad Kholili (Fakultas Ilmu Budaya, Universitas Brawijaya, 2022)
Anchored by narrative lens, the current study attempts to delve into EFL learner's exposure to utilizing Proofreader as a tool for improving English writing competency. One Indonesian EFL learner from a private University shared his experiences of the power of using Proofreader for accomplishing his tasks and for improving his writing proficiency. Written reflection and semi-structured interview were held by the researchers with the research participant. The results indicated that the EFL learner felt way more improved in their writing after using the application for learning English writing. He perceived that Proofreader application has helped him elevate their writing proficiency in terms of enriching vocabulary for writing, translating English tasks, including correcting errors in sentences, finding out contextual synonym, as well as improving readability and style